Epidemiologic analysis of sporadic Salmonella typhi isolates and those from outbreaks by pulsed-field gel electrophoresis. - Thong, Kwai Lin; Cheong, Y. M.; Puthucheary, S.; Koh, C. L.; Pang, T. (American Society for Microbiology, 1994)
Pulsed-field gel electrophoresis (PFGE) was used to compare and analyze 158 isolates of Salmonella typhi from five well-defined outbreaks of typhoid fever in Malaysia and also isolates involved in sporadic cases of typhoid fever occurring during the same period. Digestion of chromosomal DNAs from these S. typhi isolates with the restriction endonucleases XbaI (5'-TCTAGA-3'), SpeI (5'-ACTAGT-3'), and AvrII (5'-CCTAGG-3') and then PFGE produced restriction endonuclease analysis (REA) patterns consisting of 11 to 24 DNA fragments ranging in size from 20 to 630 kbp. Analysis of the REA patterns generated by PFGE after digestion with XbaI and SpeI indicated that the S. typhi isolates obtained from sporadic cases of infection were much more heterogeneous (at least 13 different REA patterns were detected; Dice coefficient, between 0.73 and 1.0) than those obtained during outbreaks of typhoid fever. The clonal nature and the close genetic identities of isolates from outbreaks in Alor Setar, Penang, Kota Kinabalu, Johor Bahru, and Kota Bahru were suggested by the fact that only a limited number of REA patterns, which mostly differed by only a single band, were detected (one to four patterns; Dice coefficient, between 0.82 and 1.0), although a different pattern was associated with each of these outbreaks. Comparison of REA patterns with ribotyping for 18 S. typhi isolates involved in sporadic cases of infection showed a good correlation, in that 72% of the isolates were in the same group. There was no clear correlation of phage types with a specific REA pattern. We conclude that PFGE of s. typhi chromosomal DNA digested with infrequently cutting restriction endonucleases is a useful method for comparing and differentiating S. typhi isolates for epidemiological purposes.